1970
DOI: 10.1029/jc075i033p06736
|View full text |Cite
|
Sign up to set email alerts
|

Examination of surfaces exposed to a noctilucent cloud, August 1, 1968

Abstract: A successful flight of a recoverable payload designed to collect particles from a noctilucent cloud was made on August 1, 1968, at 0410 local daylight time (0910 UT), from Fort Churchill, Canada. Photographs obtained by project observers at Thompson, Canada, 400 km southwest of Churchill, showed that the noctilucent cloud was over the launch site at the time of flight. Electron microscope examinations of collecting surfaces exposed above 60 km showed about 6000 particles/cm • of a certain type on surfaces faci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

1973
1973
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…A series of rocket-borne sampling devices launched in the 1960's did Published by Copernicus Publications on behalf of the European Geosciences Union. R. W. Saunders et al: Ice nucleation by refractory nanoparticles recover a variety of particulate samples from the upper atmosphere (Hemenway et al, 1963;Farlow et al, 1970) which showed a range of sizes, morphologies and compositions, although whether any of these samples could be classed as meteoric smoke remains unanswered. However, two groups of collected particles, labelled "type 2" and "type 5" in the paper of Farlow et al (1970), did show an aggregated nature and extended morphology, possibly indicative of meteoric smoke.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of rocket-borne sampling devices launched in the 1960's did Published by Copernicus Publications on behalf of the European Geosciences Union. R. W. Saunders et al: Ice nucleation by refractory nanoparticles recover a variety of particulate samples from the upper atmosphere (Hemenway et al, 1963;Farlow et al, 1970) which showed a range of sizes, morphologies and compositions, although whether any of these samples could be classed as meteoric smoke remains unanswered. However, two groups of collected particles, labelled "type 2" and "type 5" in the paper of Farlow et al (1970), did show an aggregated nature and extended morphology, possibly indicative of meteoric smoke.…”
Section: Introductionmentioning
confidence: 99%
“…R. W. Saunders et al: Ice nucleation by refractory nanoparticles recover a variety of particulate samples from the upper atmosphere (Hemenway et al, 1963;Farlow et al, 1970) which showed a range of sizes, morphologies and compositions, although whether any of these samples could be classed as meteoric smoke remains unanswered. However, two groups of collected particles, labelled "type 2" and "type 5" in the paper of Farlow et al (1970), did show an aggregated nature and extended morphology, possibly indicative of meteoric smoke. More recently, in situ measurements of positively charged particles at 80-90 km (Rapp et al, 2005) and satellite solar occultation measurements (Hervig et al, 2009) have lent further support to the presence of nano-sized meteoric smoke in the upper atmosphere, whilst line features observed in radar spectra have been shown to be consistent with the effect of charged particles present in the upper atmosphere (Strelnikova et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…A number of early attempts to sample and return NLC/PMSE particles were made (e. g. Hemenway et al, 1964Hemenway et al, , 1972Witt, 1969;Farlow et al, 1970;Ferry and Farlow, 1972;Rauser andFechtig, 1973, Havnes et al, 1996), but no such particles were firmly identified. The existence of impacting particles with halo radii ranging from 100 nm to 600 nm and solid nuclei having radii between 50 and 200 nm was claimed (Hemenway et al, 1964;Ferry and Farlow, 1972).…”
Section: Sample Return With the Meteoric Smoke Sampler (Mess)mentioning
confidence: 99%
“…On the other hand, the microphysical properties of meteoric-smoke particles are still poorly understood. This lack of knowledge is due to the complications involved with in situ measurements at mesospheric altitudes that can only be reached by sounding rockets (Farlow et al, 1970;Havnes et al, 1996;Goldberg et al, 2001;Smiley et al, 2002;Rapp et al, 2005;Lynch et al, 2005;Hedin et al, 2007b). Furthermore, the detection of nanometre-sized particles is constrained by the shock wave in front of the rocket, which may prevent small particles from reaching the detector (Hedin et al, 2007a) and by contamination from the rocket itself.…”
Section: Introductionmentioning
confidence: 99%